Analysis Of Purchasing Certificates Based On Regulations Minister Of Agrarian Spatial Planning Land Agency Number 13 Of 2017 - Ruslan, Ruslan (Legalpreneur Journal, 2023)
This paper aims to describe how the implementation of blocking Land certificate based on sweets ATR / Ka BPN number 13 of 2017 on blocking and confiscation procedures and how legal consequences of blocking the land certificate.To discuss this issue, the authors conducted the study using normative research methods. That the implementation of blocking and its stages must refer to ATR/ BPN Regulation Number 13 Year 2017 on procedures for blocking and confiscation. Where Is The Office Land should be processed as soon as possible if there is a request to block and notify applicant to register with the local District Court due to the validity period of the block only 30 (thirty) days from the date of input of the Land Office application and ends by itself. For notary / land deed officer (PPAT) for each certificate which will be carried out the transfer of rights or encumbrance in order to file application cheking first to the Land Office before making his deed PPAT, the goal is that the requested certificate is not in the process of blocking